Sosedi po planete. Italiia i Rossiia . Sosedi po planete. Italiia i Rossiia . Neighbors on the Planet. Italy and Russia . Соседи по планете. Италия и Россия - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Segment on Italian culture and art; discussion of the value of Roman law. Featured in the program: Kafanov, Leonid (Historian) Contributors: Luchai, Galina (Anchor) Сюжет о культуре и искусстве Италии; обсуждение значения римского права. В программе участвуют: Кафанов, Леонид (Историк) Создатели: Лучай, Галина (Ведущий/Ведущая)